2018
DOI: 10.1101/412379
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cross-talk between the receptor tyrosine kinases AXL and ERBB3 regulates invadopodia formation in melanoma cells

Abstract: The invasive phenotype of metastatic cancer cells is accompanied by the formation of actin-rich invadopodia, which adhere to the extracellular matrix, and degrade it.In this study, we explored the role of the tyrosine kinome in the formation of invadopodia in metastatic melanoma cells. Using a microscopy-based siRNA screen, we identified novel invadopodia regulators, the knock-down of which either suppresses (e.g., TYK2, IGFR1, ERBB3, TYRO3, FES, ALK, PTK7) or enhances invadopodia formation and function (e.g.,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 51 publications
3
21
0
Order By: Relevance
“…The AXL receptor kinase is known to play a critical role in cell proliferation, survival, cancer stem cell maintenance, and metastasis in several cancers 25 , and has been associated with melanoma cell motility, invasion, and drug resistance [30][31][32] . Thus, it represents a reasonable candidate for mediating the proinvasive effects of ST3GAL1.…”
Section: A375 M6mentioning
confidence: 99%
“…The AXL receptor kinase is known to play a critical role in cell proliferation, survival, cancer stem cell maintenance, and metastasis in several cancers 25 , and has been associated with melanoma cell motility, invasion, and drug resistance [30][31][32] . Thus, it represents a reasonable candidate for mediating the proinvasive effects of ST3GAL1.…”
Section: A375 M6mentioning
confidence: 99%
“…An increased expression of AXL in highly metastatic breast cancer was found to be essential for all steps of the metastatic process, starting with intravasation of cancer cells (Goyette et al, 2018). Consistently with the association of AXL with cancer invasion and metastasis, a very recent study of Revach et al (2019) reported that AXL may regulate the formation of invadopodia in melanoma cells. Furthermore, AXL has been linked to epithelial-tomesenchymal transition (EMT) that is associated with metastasis (Chaffer et al, 2016;Diepenbruck & Christofori, 2016).…”
Section: Introductionmentioning
confidence: 67%
“…Since mesenchymal migration of cancer cells requires constant disassembly of existing FAs and assembly of new ones, our results indicate that the GAS6-AXL signaling pathway may regulate these processes, partially by triggering the formation of CDRs. AXL was recently shown to stimulate the formation and activity of invadopodia in melanoma cells (Revach et al, 2019). This is another type of actin-based protrusions important for cancer metastasis, as they degrade and remodel the ECM (Eddy et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Receptor tyrosine kinases (RTKs) are transmembrane glycoproteins that communicate with cellular growth factors and extracellular ligands [11]. They play vital roles in intracellular tyrosine phosphorylation and intracellular signaling [12].…”
Section: Discussionmentioning
confidence: 99%